Comparative analysis of Z-score, Springate, and Zmijewski models in predicting financial distress conditions - Yendrawati, Reni; Adiwafi, Nafil (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2020)
This study aims at finding the accuracy level of financial distress prediction on companies in the property, real estate, and building construction sectors. The financial distress prediction models employed here are Z-score, Springate, and Zmijewski. The research population involved all property companies registered at the Indonesian Stock Exchange in the period of 2014-2018. Purposive sampling was used to collect 45 companies. The number of observations taken was 225. The data used were the secondary data taken from the Indonesian Stock Exchange website. The findings showed that the models with high accuracy to predict financial distress in the property, real estate, and building construction sector were the Altman Z-Score model, followed by Zmijewski and Springate models.